Sistem Otomatis Pengisian Air Minum untuk Tunanetra Berbasis Arduino Uno - akbar hendra (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2021)
The research aims to develop an arduino-based intelligent system that can help the visually impaired in controlling the volume of water. The system design method uses ultrasonic sensors and voice rekording modules. The results of this study showed effective results in helping the visually impaired and have a fast response time of about 2.20 seconds from the measurable glass volume condition by using the arduino uno R3 microcontroller as the main device equipped with several devices such as voice recording modules and HCSR-04 sensors.